Clinical presentation, treatment, and antimicrobial susceptibility of 155 sequential Staphylococcus lugdunensis infections - Kurt D. Palumbo; Natasia F. Jacko; Michael Z. David (Microbiology Spectrum)
ABSTRACT Staphylococcus lugdunensis is known to be virulent, but there are few large-scale epidemiologic studies of this species to define types of infection, susceptibility patterns, and severity. S. lugdunensis isolates from any culture at four U.S. tertiary care hospitals between 1 April 2021 and 1 April 2022 were identified. For the first isolate from each subject, clinical, demographic, and outcome data were recorded. Of 291 isolates, 223 were obtained from a clinically significant infection. Of these 223 isolates, 86 (38.6%) were from monomicrobial cultures; additionally, S. lugdunensis was considered a true pathogen in 69/137 polymicrobial infections. Among 155 subjects with S. lugdunensis infections, 49.7% were female, 46.5% were black, and 41.9% were white; 51.6% of infections were community associated. The most common infection sites were skin and soft tissue (SSTI) (n = 98, 63.2%), urinary tract (n = 16, 10.3%), and sinusitis (n = 14, 9%). Of nine monomicrobial bloodstream infections (BSIs), two were fatal, three involved foreign bodies, and two had infective endocarditis. Greater than half of SSTIs required an invasive procedure for cure. Among 138/291 isolates from colonization or infection, tetracycline, trimethoprim-sulfamethoxazole, oxacillin, and vancomycin susceptibility rates were 94.8% (128/135), 95.9% (94/98), 84.1% (116/138), and 100% (138/138), respectively. There were similarities in types of infection comparing S. lugdunensis in this study and prior reports on Staphylococcus aureus. SSTI was the predominant S. lugdunensis infection type; more than 50% of SSTIs required procedural intervention. Of nine BSIs, three involved a foreign body, and there were two cases of infective endocarditis. Oxacillin resistance was identified in 16% of isolates.IMPORTANCEIn recent years, Staphylococcus lugdunensis has been identified with increasing frequency as a human pathogen causing a wide variety of clinical syndromes, from soft tissue infections to fatal cases of bloodstream infection. Despite this, there are few large-scale epidemiologic studies examining this highly virulent organism. Our study adds to the growing literature on this emerging pathogen by analyzing a large case series of sequential S. lugdunensis infections at four U.S. hospitals to define its contemporary epidemiology, including the types of infections it causes, their outcomes, treatment approaches, and antimicrobial susceptibilities. These data provide valuable insights for clinicians in diagnosing and treating patients with these often debilitating infections. The findings also improve upon our understanding of the incidence of each infection syndrome and variability in antimicrobial susceptibilities of isolates to guide the design of future studies on the genomic epidemiology of this important pathogen.